Population structure of Lingula (Bruguière, 1791) in Alue Naga waters, Banda Aceh City, Indonesia - Chitra Octavina; Maria Ulfah; Sri Agustina; Haekal Azief Haridhi; Ade Yudistira (Depik, 2021)
Lingula sp. is one of the genera of the Brachiopoda phylum that lives in the intertidal zone or areas that are affected by tides. The purpose of this study was to determine the population structure of Lingula sp. through the approach of population structure, density, distribution patterns, length and weight relationship and with physical and chemical parameters in the waters of Alue Naga, Syiah Kuala District, Banda Aceh City. The method used in this research is a purposive random sampling method. The results show that the growth pattern of Lingula sp. is classified as negative allometric at three research sites in Alue Naga waters, based on the value of b 3. The density of Lingula sp. was the highest at site 1 with a total of 17.7 ind/m2. While the density of Lingula sp. was the lowest at site 3 with a total of 9.7 ind/m2. The distribution of Lingula sp. at the three sites were uniform, with morisita index (Id) values of 0.352, 0.257, and 0.208 for sites 1, 2, and 3 respectively. In addition, the environmental factors of the three research sites in Alue Naga waters are within the normal limits of life for Lingula sp.Keywords: Alue NagaLingula sp. Population structure